2023
DOI: 10.1038/s41467-023-37883-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and stabilization of EZH2 by DCAF1/VprBP trigger aberrant gene silencing in colon cancer

Abstract: Our recent work has shown that DCAF1 (also known as VprBP) is overexpressed in colon cancer and phosphorylates histone H2AT120 to drive epigenetic gene inactivation and oncogenic transformation. We have extended these observations by investigating whether DCAF1 also phosphorylates non-histone proteins as an additional mechanism linking its kinase activity to colon cancer development. We now demonstrate that DCAF1 phosphorylates EZH2 at T367 to augment its nuclear stabilization and enzymatic activity in colon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Because some histone modi cations such as acetylation activates transcription, opposite to the transrepressive effects of H2AT120p, future work examining melanomagenic transcription program should also focus on the competitive action of factors depositing active histone marks against VprBP. Related, our recent investigation revealed additional role for VprBP in phosphorylating EZH2 in colon cancer cells and established another epigenetic process underlying VprBP-induced oncogenic gene silencing program [32]. While a potential involvement of VprBP-mediated EZH2 phosphorylation in melanomagenesis was not explored in the current study, stable depletion and inhibition of VprBP in melanoma cells expressing low levels of EZH2 still generated a substantial increase in melanomagenic gene transcription and cell growth rates (data not shown), lending support to the notion that the pro-melanomagenic activity of VprBP is mainly through H2AT120p at target genes.…”
Section: Discussionmentioning
confidence: 72%
“…Because some histone modi cations such as acetylation activates transcription, opposite to the transrepressive effects of H2AT120p, future work examining melanomagenic transcription program should also focus on the competitive action of factors depositing active histone marks against VprBP. Related, our recent investigation revealed additional role for VprBP in phosphorylating EZH2 in colon cancer cells and established another epigenetic process underlying VprBP-induced oncogenic gene silencing program [32]. While a potential involvement of VprBP-mediated EZH2 phosphorylation in melanomagenesis was not explored in the current study, stable depletion and inhibition of VprBP in melanoma cells expressing low levels of EZH2 still generated a substantial increase in melanomagenic gene transcription and cell growth rates (data not shown), lending support to the notion that the pro-melanomagenic activity of VprBP is mainly through H2AT120p at target genes.…”
Section: Discussionmentioning
confidence: 72%
“…A very recent study demonstrated DCAF1 mediated phosphorylation of EZH2 at T367 to augment its nuclear stabilization and enzymatic activity in colon cancer cells. Such DCAF1-mediated EZH2 phosphorylation followed by nuclear localization led to elevated levels of H3K27me3 and altered expression of growth regulatory genes in cancer cells 30 . In contrast, herein we report that S-nitrosylation of C329 residue of EZH2 caused its cytosolic localization followed by lysosomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Because some histone modifications such as acetylation activates transcription, opposite to the trans-repressive effects of H2AT120p, future work examining melanomagenic transcription program should also focus on the competitive action of factors depositing active histone marks against VprBP. Related, our recent investigation revealed additional role for VprBP in phosphorylating EZH2 in colon cancer cells and established another epigenetic process underlying VprBP-induced oncogenic gene silencing program [ 32 ]. While a potential involvement of VprBP-mediated EZH2 phosphorylation in melanomagenesis was not explored in the current study, stable depletion and inhibition of VprBP in melanoma cells expressing low levels of EZH2 still generated a substantial increase in melanomagenic gene transcription and cell growth rates (data not shown), lending support to the notion that the pro-melanomagenic activity of VprBP is mainly through H2AT120p at target genes.…”
Section: Discussionmentioning
confidence: 99%